2014
DOI: 10.1002/ppsc.201400036
|View full text |Cite
|
Sign up to set email alerts
|

High‐Density Lipoprotein Nanoparticles Deliver RNAi to Endothelial Cells to Inhibit Angiogenesis

Abstract: Systemic delivery of therapeutic nucleic acids to target cells and tissues outside of the liver remains a major challenge. We synthesized a biomimetic high density lipoprotein nanoparticle (HDL NP) for delivery of a cholesteryl modified therapeutic nucleic acid (RNAi) to vascular endothelial cells, a cell type naturally targeted by HDL. HDL NPs adsorb cholesteryl modified oligonucleotides and protect them from nuclease degradation. As proof of principle, we delivered RNAi targeting vascular endothelial growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 39 publications
1
27
0
Order By: Relevance
“…These HDL nanoparticles were also shown to bind cholesterylated RNA, which was effective at reducing the cellular expression of vascular endothelial growth factor receptor 2 (VEGFR2). [206] Systemic administration of these conjugates resulted in decreased VEFGR2 expression in SR-B1 expressing cells, leading to decreased angiogenesis and a marked reduction in the volume of lung tumor xenografts. [206] Regardless of the type of nucleic acid adsorbed to the surface of this HDL platform, no toxicity was observed in normal, healthy cells and tissues both in vitro and in vivo .…”
Section: Nucleic Acid Delivery With Lipoproteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…These HDL nanoparticles were also shown to bind cholesterylated RNA, which was effective at reducing the cellular expression of vascular endothelial growth factor receptor 2 (VEGFR2). [206] Systemic administration of these conjugates resulted in decreased VEFGR2 expression in SR-B1 expressing cells, leading to decreased angiogenesis and a marked reduction in the volume of lung tumor xenografts. [206] Regardless of the type of nucleic acid adsorbed to the surface of this HDL platform, no toxicity was observed in normal, healthy cells and tissues both in vitro and in vivo .…”
Section: Nucleic Acid Delivery With Lipoproteinsmentioning
confidence: 99%
“…[206] Systemic administration of these conjugates resulted in decreased VEFGR2 expression in SR-B1 expressing cells, leading to decreased angiogenesis and a marked reduction in the volume of lung tumor xenografts. [206] Regardless of the type of nucleic acid adsorbed to the surface of this HDL platform, no toxicity was observed in normal, healthy cells and tissues both in vitro and in vivo . [92, 206] These studies indicate that gold core HDL is an excellent carrier for therapeutic nucleic acids.…”
Section: Nucleic Acid Delivery With Lipoproteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tripathy et al then demonstrated that gold nanoparticle templated spherical HDL can formulate cholesterylated antisense RNA. 81 In the system tested, antisense RNA to vascular endothelial growth factor receptor 2 (VEGFR2) could knockdown VEGFR2 mRNA levels and reduce endothelial survival and morphogenesis. Further data demonstrate that delivery of the HDL NP conjugates is dependent on expression of SR-B1.…”
Section: Mimics Of Spherical Hdl For Drug Deliverymentioning
confidence: 99%
“…916 In particular, the surface of carriers coated with Abs to the cell adhesion molecule PECAM (platelet endothelial cell adhesion molecule 1, PECAM-1, CD31) enables endothelial delivery of NCs, improving therapeutic effects of their drug cargoes in animal models. 1721 These encouraging results justify further optimization of endothelial targeting and effect of anti-PECAM/NC (indicated as Ab/NC unless indicated otherwise).…”
mentioning
confidence: 99%